Governing America history, culture, institutions, organisation, policy - Hames, Tim; Rae, Nicol (Manchester Univ. Press, 1996)
"In this brand new, fully up-to-date textbook, Tim Hames and Nicol Rae provide a complete introduction to the American system of government. They take the student reader through from the founding fathers to Clinton's foreign policy, building an understanding of how American politics works on a knowledge of the historical and cultural influences that shape American society." "The first section gives an overview of American political history, and focuses on the incidents which have shaped the nation's political culture. The second examines the major political institutions: the Presidency, Congress, the Supreme Court, and state and local government. Other vital elements in the governmental system - the federal bureaucracy, mass media, political parties and interest groups - are then fully discussed. The final section analyses the effect of all these conflicting influences on elections for public office, and the two crucial policy arenas of the economy and foreign affairs." "The book concludes with a discussion of America on the verge of the twenty-first century. Throughout, boxes expand and develop the text with fascinating case studies and visual material."--BOOK JACKET.